Graphene based hyperbolic metamaterial for tunable mid-infrared biosensing. Issue 14 (17th February 2021) - Cynthia, Sarah; Ahmed, Rajib; Islam, Sharnali; Ali, Khaleda; Hossain, Mainul
Abstract : Graphene/Al2 O3 HMM stack, coupled to a gold grating structure, for tunable, label-free, and highly sensitive biosensing in the mid-IR wavelength region. FDTD simulations show that the proposed device can achieve a maximum sensitivity of 4052 nm RIU −1 . Abstract : Plasmonic biosensors, operating in the mid-infrared (mid-IR) region, are well-suited for highly specific and label-free optical biosensing. The principle of operation is based on detecting the shift in resonance wavelength caused by the interaction of biomolecules with the surrounding medium. However, metallic plasmonic biosensors suffer from poor signal transduction and high optical losses in the mid-IR range, leading to low sensitivity. Here, we introduce a hyperbolic metamaterial (HMM) biosensor, that exploits the strong, tunable, mid-IR localization of graphene plasmons, for detecting nanometric biomolecules with high sensitivity. The HMM stack consists of alternating graphene/Al2 O3 multilayers, on top of a gold grating structure with rounded corners, to produce plasmonic hotspots and enhance sensing performance. Sensitivity and figure-of-merit (FOM) can be systematically tuned, by varying the structural parameters of the HMM stack and the doping levels (Fermi energy) in graphene. Finite-difference time-domain (FDTD) analysis demonstrates that the proposed biosensor can achieve sensitivities as high as 4052 nm RIU −1 (refractive index unit) with a FOM of 11.44 RIU −1 . We anticipate that the reported graphene/Al2 O3 HMM device will find potential application as a mid-IR, highly sensitive plasmonic biosensor, for tunable and label-free detection.